Spatial distribution and temporal variation of high fluoride contents in groundwater and prevalence of fluorosis in humans in Yuanmou County, southwest China - Chen, H.F.; Yan M; Yang XF; Chen, Z.; Wang GA; Schmidt-Vogt, D.; Xu YF; Xu, J.C. (Elsevier, 2012)
Successive surveys conducted in 1984, 2006 and 2007, of all villages in Yuanmou County, China, highlighted 40 villages with groundwater fluoride levels higher than 1.0mg/L and related cases of human fluorosis. Using the data from these surveys and by employing geographic information system (GIS) techniques, high fluoride levels and fluorosis cases were mapped. The results show high fluoride concentrations and fluorosis hotspots were found to be predominately located in the lowlands of central Yuanmou County. Spatial distribution of high fluoride levels was found to be primarily determined by geology, arid climate, and topography. Both dental and skeletal fluorosis had dramatically decreased due to a program of low-fluoride drinking water supply supported by local governments. The prevalence of dental fluorosis in children had dropped from 43.26% in 1984 to 21.97% in 2006, and the number of skeletal fluorosis cases had decreased from 327 in 1984 to 148 in 2006, respectively. Despite a decline in fluorosis cases, the emergence of fluorosis in new areas indicates the need for both continuous monitoring of drinking water in affected areas and increased public awareness.